2019
DOI: 10.1016/j.jddst.2019.101219
|View full text |Cite
|
Sign up to set email alerts
|

Cationic niosome-based hBMP7 gene transfection of neuronal precursor NT2 cells to reduce the migration of glioma cells in vitro

Abstract: This study explores interesting complementary approaches in cellbased hBMP7 gene delivery in order to mitigate the migration of glioblastoma cells based on the idea that this human bone morphogenetic protein (hBMP7) has enormous therapeutic potential in curing brain injuries as well as malignancies. After physicochemical characterization, the non-viral cationic niosomes were complexed with pUNO1-hBMP7 plasmids and used to transfect neuronal precursor NT2 cells. Subsequently, the transfected cells were co-cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Therefore, two niosome formulations that differed only regarding the presence or absence of the non-ionic surfactant poloxamer 188 were elaborated by the reverse-phase evaporation technique and characterized to deliver the genetic material into the rat brain cortex. When poloxamer 188 was incorporated into the niosomes, the sizes of niosomes increased, which was probably due to the high HLB value of poloxamer 188 and to the interaction with the cationic lipid [161]. However, no significant change in zeta potential was reported, being over +40 mV.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…Therefore, two niosome formulations that differed only regarding the presence or absence of the non-ionic surfactant poloxamer 188 were elaborated by the reverse-phase evaporation technique and characterized to deliver the genetic material into the rat brain cortex. When poloxamer 188 was incorporated into the niosomes, the sizes of niosomes increased, which was probably due to the high HLB value of poloxamer 188 and to the interaction with the cationic lipid [161]. However, no significant change in zeta potential was reported, being over +40 mV.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…Consequently, the closed bilayer structure of niosomes has hydrophilic inner and outer surfaces, with a sandwiched lipophilic area in between. The non-ionic surfactants are safe and affordable for the use in biomedicine as carriers for genes or hydrophilic/hydrophobic drugs [74]. Niosomes are prepared by various methods, such as ether injection, sonication, and microfluidics, to mention a few [75].…”
Section: Niosomesmentioning
confidence: 99%
“…Therefore, it was characterized by its ability to induce the differentiation of brain tumor stem cells. Attia et al [ 165 ] demonstrated human teratocarcinoma NTERA2/D1(NT2) cells transfected with hBMP7 nioplexes are a potential treatment vehicle for GB. The in vitro study exemplified the ability of BMP7-expressing neural precursor cells to lessen the tumorigenicity of glioma cells [ 165 ].…”
Section: Cell Therapy For Glioblastomamentioning
confidence: 99%